"Crouching Tiger, Hidden Power": A 25-year Strategic Advocacy Voyage of an Environmental NGO in China. (December 2022) - Zhuang, Hao; Zinda, John A.; Lassoie, James P.
Advocacy by civil society organizations such as non-governmental organizations (NGOs) is especially challenging in a constraining political context. The Government of China has invited such organizations to assist in addressing emergent environmental problems while also limiting political challenges from them. NGOs need to respond to these political externalities strategically. This paper navigates a quarter-century advocacy voyage by an iconic Chinese environmental NGO—Friends of Nature—discussing how the organization adapted to meet internal organization challenges within a dynamic, restrictive political environment. We found two major strategic pathways: first, diminishing dependency on influential individual leaders by building institutional competence and reputation; second, strategic specialization in litigation that anticipates opportunities that might emerge as state policies shift, and actively shaping niches to exert impact. This study adds historical insights on an NGO's evolution in China that can benefit other civil society organizations that face significant political, social, or legal challenges.